2008
DOI: 10.1007/s12032-008-9109-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression protein profiles of lung squamous carcinoma cell using shot-gun proteomics strategy

Abstract: The aim of this study is to globally screen and identify the expression protein profiles of lung squamous carcinoma cell (SqCC) using shot-gun proteomics strategy and to further analyze function of individual proteins by bioinformatics, which may likely result in the identification of new biomarkers and provide helpful clues for pathogenesis, early diagnosis, and progression of lung SqCC. The specific tumor cells were isolated and collected from the tissues of six patients with lung SqCC by laser capture micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…One recent study using a shot-gun proteomics strategy showed that PHB is a candidate protein for a biomarker of lung SqCC [28]. A few other proteomics analysis studies focused on the correlation between altered expression of proteins and drug resistance in lung cancer cell lines [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study using a shot-gun proteomics strategy showed that PHB is a candidate protein for a biomarker of lung SqCC [28]. A few other proteomics analysis studies focused on the correlation between altered expression of proteins and drug resistance in lung cancer cell lines [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2D-DIGE and quantitative gel-free mass spectrometry approaches have been coupled to LCM for proteomic analyses of distinct, pure cell populations (Shekouh et al 2003; Li et al 2004; Zang et al 2004; Haqqani et al 2005; Bagnato et al 2007; Mustafa et al 2008; Patel et al 2008; Wang et al 2008; Zhang and Koay 2008; Nan et al 2009; Scicchitano et al 2009; Waanders et al 2009; Yao et al 2009; Asomugha et al 2010; Zhang et al 2010). Other methods such as punch biopsy can be used to microdissect tissues for subsequent proteomic analyses (Folli et al 2010), but because it is difficult to see the three-dimensional boundaries of structures from the surface of the tissue, punch biopsies can sample adjacent regions that are not of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis The ANXA1 might play an important role in lung squamous cell carcinoma genesis, progression, recurrence, and metastasis and might be used as markers of this carcinoma (Nan et al, 2009). …”
Section: Diseasementioning
confidence: 99%